2020
DOI: 10.1186/s12870-020-2290-0
|View full text |Cite
|
Sign up to set email alerts
|

Global identification and analysis revealed differentially expressed lncRNAs associated with meiosis and low fertility in autotetraploid rice

Abstract: Background: Autotetraploid rice is a useful germplasm for polyploid rice breeding. Our previous research showed that non-coding RNAs might be associated with low fertility in autotetraploid rice. However, little information is available on long non-coding RNAs (lncRNAs) involved in the low fertility of autotetraploid rice. In the present study, RNA-seq was employed to detect the differentially expressed meiosis-related lncRNAs in autotetraploid rice, and gene overexpression and knock out experiments were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 81 publications
(133 reference statements)
2
32
0
Order By: Relevance
“…Here, we found that almost 30% of the triticale lncRNAs possessed exons with similarity to TEs. This is in accordance with previous reports on rice [ 79 ], where 73% lncRNAs were found to overlap with different TEs. Furthermore, 9.18% of sunflower lncRNAs have TE-related exons [ 80 ].…”
Section: Discussionsupporting
confidence: 94%
“…Here, we found that almost 30% of the triticale lncRNAs possessed exons with similarity to TEs. This is in accordance with previous reports on rice [ 79 ], where 73% lncRNAs were found to overlap with different TEs. Furthermore, 9.18% of sunflower lncRNAs have TE-related exons [ 80 ].…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, compared to its wild relative, meiotic recombination was shown to be higher in cultivated sunflower and many long non-coding RNAs (lncRNAs) were exclusively up-regulated in its meiocytes ( Flórez-Zapata et al, 2016 ). Similarly, low fertility in autotetraploid rice was attributed to differential expression of lncRNAs during anther and ovule meiosis ( Li et al, 2020 ). LncRNAs are poorly characterized compared to protein-coding genes but these studies highlight their potential importance during development ( Ponting et al, 2009 ; Ariel et al, 2015 ; Shafiq et al, 2016 ) including their regulatory role during sexual reproduction ( Golicz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The processing of a subset of lncRNAs has been shown to generate small RNAs in animals ( Jalali et al, 2012 ) and plants ( Ma et al, 2014 ). Although the regulation of gene expression by small RNA has been reported in cotton anthers ( Chen et al, 2018 ), Arabidopsis meiocytes ( Huang et al, 2019 ) and rice ovules ( Li et al, 2020 ), the full integration of small RNAs and lncRNAs biogenesis and function remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In autotetraploid rice, 24 nt TEs-siRNAs could cause genome instability and sterility. On the other hand, Li et al pointed out that the differential expression level of lncRNAs was related to transposable factors and meiotic regulatory targets, which may be the endogenous noncoding regulatory factors of pollen/embryo sac development in autotetraploid rice [131,132]. They also found that the low fertility of autotetraploid rice was caused not only by the differential expression of pollen development related genes, but also by sequence variation and differential methylation.…”
Section: The Molecular Mechanism Of Polyploid Rice Fertilitymentioning
confidence: 99%